MENYOAL PROFESIONALISME GURU PROFESIONAL: SEBUAH TELAAH KRITIS - Almu'tasim, Amru (J-PAI: Jurnal Pendidikan Agama Islam, 2016)
Teacher is a designation for the position, position and profession for someone who devoted himself in the field of education through educational interaction patterned, formal, and systematic (Surya, 1998). Historically professorship connote uplifted services (noblest vocation). They named the child paedagogos or waiters, waitresses humanizing honorable man, or man of human beings (gogos humanities). Guru is one of the human component in the teaching-learning process, which had a role in the formation of human resources business potential in development. Therefore, teachers must be someone who can 'digugu' and 'imitated'. Teachers must participate actively and putting his position as professionals, in accordance with the demands of the growing community.Â Keywords: professionalism, professional teacher